Răspuns :
a+b+c=9400
a=b-1800 → b=a+1800
a=c+500 → c=a-500
a+(a+1800)+(a-500)=
=9400 →
→ 3*a+1800-500=9400→
→ 3*a+1300=9400 →
→ 3*a=9400-1300 →
→ a=8100:3 →
→ a=2700
b=a+1800=2700+1800=
=4500
c=a-500=2700-500=
=2200
a=b-1800 → b=a+1800
a=c+500 → c=a-500
a+(a+1800)+(a-500)=
=9400 →
→ 3*a+1800-500=9400→
→ 3*a+1300=9400 →
→ 3*a=9400-1300 →
→ a=8100:3 →
→ a=2700
b=a+1800=2700+1800=
=4500
c=a-500=2700-500=
=2200
a+b+c= 9400
a= b - 1800 ;⇒ b= 1800+a
a= c+500 ⇒ c= a-500
inlocuim:
a+1800+a+ a-500= 9400
3a= 9400- 1300
3a= 8100
a=8100:3
a= 2700
b= 1800+a
b= 1800+2700
b= 4500
c= a-500
c=2700-500
c= 2200
Verificam:
2700+4500+2200= 9400
a= b - 1800 ;⇒ b= 1800+a
a= c+500 ⇒ c= a-500
inlocuim:
a+1800+a+ a-500= 9400
3a= 9400- 1300
3a= 8100
a=8100:3
a= 2700
b= 1800+a
b= 1800+2700
b= 4500
c= a-500
c=2700-500
c= 2200
Verificam:
2700+4500+2200= 9400